Evaluation of a fermented palm kernel meal as a prebiotic for enhancing immune response in Indonesian red claw crayfish (Cherax quadricarinatus) - Diki Danar Tri Winanti; Hilma Nahwa Firdausi; Maulid Wahid Yusup; Putu Cinthia Delis; Agus Setyawan; Yeni Elisdiana; Hilma Putri Fidyandini; Muhammad Kholiqul Amiin; Ari Widodo (Veterinary World)
Background and Aim: The Indonesian red claw crayfish (Cherax quadricarinatus) represents a significant aquaculture commodity with substantial economic importance; however, disease outbreaks, particularly tail ulceration caused by Aeromonas hydrophila, pose challenges to sustainable production. This study evaluated the efficacy of fermented palm kernel meal (FPKM), rich in mannan oligosaccharides, as a prebiotic additive to enhance non-specific immune responses in C. quadricarinatus.